De-Risking Building Performance Investments by Certified Quality Management Services (QUEST) - Martinac, Ivo; Song, Han-Suck; Plesser, Stefan; Ryan, Cormac; Teisen, Ole; Wen, Jin (CLIMA 2022 conference, 2022)
Non-compliance with predicted, contracted or otherwise required aspects and levels of building performance can result in a wide range of problems. This includes sub-par quality of building functions and services, unsatisfactory indoor environmental quality, disappointing end-user experience, excessive energy use, excessive environmental emissions, increased maintenance and operational costs, operational start-up loss, component and system faults, difficulties in achieving targeted building certification levels, mismatch with business case, lack of adaptability and flexibility, expenses changed from capital expenditure to operational expenditure, facility not meeting regulatory requirements, as well as increased risk and liability. This is often referred to as the building performance gap. Compliance with ambitious levels of resource efficiency, energy performance, decarbonisation and circularity goals, as well as other key objectives defined by the EU Taxonomy for sustainable activities will be essential criteria for the sustained future success of businesses throughout the building sector. Building performance investments, including investments in energy efficiency, can generate significant environmental benefits, while also increasing financial returns. The key goal of the EU-funded project Quality Management Investments for Energy Efficiency (QUEST) is to promote private investments and financing in quality management services to ensure sustainability and energy-efficiency of building projects. To that end, a toolkit, with the QUEST data engine as the core data source, has been developed that will enable financial institutions to determine key factors influencing risk in the design, development and operations of energy-efficiency and sustainability projects, as well as the impact of quality management services. This will allow them to reduce risk, increase financial performance and therefore significantly increase investment volumes.